1986
DOI: 10.1038/bjc.1986.31
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MHC class II antigens in human B-cell leukaemia and non-Hodgkin's lymphoma

Abstract: Suggestions that human MHC class II antigens might be differentiation markers of leukaemic cells (Schlossman et al., 1976), and the demonstration that class II antigen expression is lost at the terminal stages of B cell differentiation, in both normal and malignant cells (Halper et al., 1978) date back almost a decade. These findings preceded the realization that MHC class II antigens are encoded by a large number of genes (Korman et al., 1985;. Recent detailed molecular studies of the structure of class II an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…Interestingly, loss of human leukocyte antigen (HLA) class I and class II expression has been described in a subset of aggressive B-cell lymphomas (consisting primarily of DLBCLs), and this loss correlated with extranodal disease 71 and poor survival. [72][73][74] Similarly, a recent study of 258 DLBCLs found extensive loss of heterozygosity within the HLA region on the p arm of chromosome 6, primarily in extranodal lymphomas. 75 The authors of this study also speculated that a structural loss of HLA class I and II gene expression might contribute to escape of aggressive B-cell lymphomas from immune surveillance.…”
Section: Expression Profiling Of T(14;18)-positive Cell Lines 131mentioning
confidence: 89%
“…Interestingly, loss of human leukocyte antigen (HLA) class I and class II expression has been described in a subset of aggressive B-cell lymphomas (consisting primarily of DLBCLs), and this loss correlated with extranodal disease 71 and poor survival. [72][73][74] Similarly, a recent study of 258 DLBCLs found extensive loss of heterozygosity within the HLA region on the p arm of chromosome 6, primarily in extranodal lymphomas. 75 The authors of this study also speculated that a structural loss of HLA class I and II gene expression might contribute to escape of aggressive B-cell lymphomas from immune surveillance.…”
Section: Expression Profiling Of T(14;18)-positive Cell Lines 131mentioning
confidence: 89%
“…The study of the epigenetic regulation of the Master Regulator CIITA is clinically relevant, as aberrant expression of CIITA leads to inappropriate expression of MHC II proteins. [26][27][28] Dysregulated expression of MHC II is associated with various disorders and diseases; in sum, overexpression of MHC II is correlated with autoimmune diseases, while suppression of MHC II expression leads to tumor development and immune deficiency syndromes.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…In contrast, E-myc tumors express very low levels of MHC II (supplemental Figure 1), consistent with aberrant MHC II expression in many human B-cell malignancies. 40 In this regard, E-myc tumor immunogenicity more closely resembles human B-cell lymphomas than A20 tumors. Similarly, it is unclear why CD8 T cells were critical for inhibition of E-myc but not A20 tumor growth after vaccination, but this may also be explained by the differences in MHC class I expression.…”
mentioning
confidence: 99%